THE EFFECT OF TEACHER AND STUDENT MOTIVATION ON ARABIC LEARNING ACHIEVEMENT IN MADRASAH IBTIDAIYAH - Nadzirotusholihah, N; Mujiburrohman, M; Fatimah, Meti (Proceeding of International Conference of Islamic Education, 2023)
The aims of this study were: 1) To determine the analysis of the effect of motivation on learning outcomes in Arabic subjects; 2) To determine the analysis of the effect of student achievement on learning outcomes in Arabic subjects at MI Muhammadiyah Karanglo Guli Nogosari Boyolali; 3) To find out the analysis of the influence of motivation on student achievement in class V in the Arabic language subject for MI Muhammadiyah Karanglo Guli Nogosari Boyolali students. This research method uses quantitative with regression analysis and hypothesis taking. The results of the research are data analysis used to analyze multiple linear regression, the results of the equation Y = 7.981 + 0.233 X1 + 0.032 X2 are obtained. The results of hypothesis testing I show that the results of data analysis show the value of tcount (3.194) > ttable (2.056), then the research hypothesis I is accepted. The results of testing hypothesis II show that the results of data analysis show the value of tcount (2.063) > ttable (2.056), then the research hypothesis II is accepted. The results of testing the third hypothesis of the study show that the value of Fcount (4.789) > Ftable (3.35), so the research statement of hypothesis III is accepted, then the third hypothesis shows that motivation and student achievement significantly and simultaneously affects the learning outcomes of language subjects Arabic at MI Muhammadiyah Karanglo Guli Nogosari Boyolali. The value of the coefficient of determination (adjusted R Square) is 0.284 or 28.4%. This value can be interpreted that the independent variable in this case the motivation and learning achievement of students is able to increase the dependent variable (learning outcomes in Arabic language subjects) by 28.4% while the rest is 71.6% (100% -28.4%), influenced by other variables not examined, for example, encouragement to learn and motivation to learn from parents, oneself in the spirit of learning Arabic